1998
DOI: 10.1161/01.cir.97.17.1675
|View full text |Cite
|
Sign up to set email alerts
|

Association of Virulent Helicobacter pylori Strains With Ischemic Heart Disease

Abstract: The association between Helicobacter pylori and ischemic heart disease seems to be due to a higher prevalence of more virulent Helicobacter strains in patients. These results support the hypothesis that Helicobacter pylori may influence atherogenesis through low-grade, persistent inflammatory stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
166
4
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(184 citation statements)
references
References 27 publications
9
166
4
5
Order By: Relevance
“…25,26 In most but not all seroepidemiological evaluations, subjects with a prominent immune response to C pneumoniae or (virulent strains of) H pylori, as indicative of chronic infection status, faced an excess risk of coronary heart disease, stroke, and vascular death. 7,[13][14][15][27][28][29] Finally, chronic bronchitis, as defined by self-reported clinical symptoms, and periodontal disease have LR denotes likelihood ratio. ORs were derived from multiple stepwise logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 In most but not all seroepidemiological evaluations, subjects with a prominent immune response to C pneumoniae or (virulent strains of) H pylori, as indicative of chronic infection status, faced an excess risk of coronary heart disease, stroke, and vascular death. 7,[13][14][15][27][28][29] Finally, chronic bronchitis, as defined by self-reported clinical symptoms, and periodontal disease have LR denotes likelihood ratio. ORs were derived from multiple stepwise logistic regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…4 -8,31 Among subjects with chronic infections, risk of atherosclerosis tended to be higher in those with a prominent inflammatory response (Figure 3), which may indicate high virulence of the underlying pathogen or atherogenic host-pathogen interactions. 13,14,27,31 Induction of systemic inflammation has been proposed to be of pathogenetic relevance in the association of infection and atherosclerosis and may rely in part on the endothelial toxicity of bacterial endotoxin and the action of proinflammatory cytokines. 7,19 Recently, we demonstrated that in smokers and subjects with chronic infections, high concentrations of circulating endotoxin predict a substantially increased risk of atherosclerosis (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Second, H pylori strains bearing the cytotoxin-associated gene A seem to be more decisive for their pathogenic contribution in atherosclerosis, although the mechanisms are unknown. 21,25 Moreover, smoking is a stress factor for endothelial cells. Evidence has indicated that both active and passive cigarette smoking is associated with endothelial dysfunction, and endothelial abnormalities may predispose to the atherogenic and thrombotic problems associated with cigarette smoking.…”
Section: Zhu Et Almentioning
confidence: 99%
“…Thus, there is a possibility that the pharmacokinetics of pitavastatin might be modified by H. pyloriinduced severe chronic gastritis. Some infectious diseases, such as Chlamydia pneumoniae infection, have been considered as risk factors for coronary heart disease (18), and several studies have pointed to an association between H. pylori infection and vascular changes due to the alteration of the serum lipid profile (19,38). Previous studies reported that the serum T-Chol, TG, or LDL concentrations in H. pylori-infected persons are significantly elevated over those in noninfected individuals (39,40).…”
Section: Discussionmentioning
confidence: 99%